Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen di PT. Indomaret Pattimura Koota Gunungsitoli - Liberti Daeli; Idarni harefa; Yupiter Mendrofa; Emanuel Zebua (LPPM Universitas HKBP Nommensen, 2024)
Business activities such as minimarkets are now an interesting phenomenon. Businesses are currently experiencing increasingly fierce competition, so it is mandatory for businesses to improve the quality of their business in order to excel in competitive competition. PT. Indomaret Pattimura Gunungsitoli City must consider consumer satisfaction. In business competition, customer satisfaction is very important. If the desired results do not meet expectations, customer dissatisfaction arises. Customer satisfaction is viewed from the customer's perspective, namely how customers feel the service provided compared to what they want. If an industry or service company does not really understand what its customers expect, customer satisfaction with the product or service is something that is difficult to achieve. Efforts to meet consumer needs and expectations are very important because in a business one of the keys to success is consumers, service quality and price are very important things to help businesses improve their business. Service quality can create comfort for consumers who shop and feel satisfied, resulting in repeat purchases. And price can also be the value determined by the company in return for the goods or services sold. In other words, price can determine purchasing decisions. This research aims to analyze the influence of service quality and price on consumer satisfaction at PT Indomaret Pattimura, Gunungsitoli City. Service quality and price are important factors that influence consumer decisions in choosing a place to shop. Service quality is measured through five dimensions: reliability, empathy, responsiveness, tangibility and assurance. This research uses quantitative methods with data collection techniques through questionnaires distributed to 100 Indomaret Pattimura consumers. Data analysis was carried out using SPSS software with multiple linear regression methods to see the simultaneous and partial influence of service quality and price variables on consumer satisfaction. The research results show that service quality and price simultaneously have a significant influence on consumer satisfaction. Partially, these two variables also have a significant positive influence on consumer satisfaction. The conclusion of this research is that PT Indomaret Pattimura needs to maintain and improve service quality and offer competitive prices to increase consumer satisfaction. Suggestions for further research are to expand the research location and include other variables that might influence consumer satisfaction.